Affective Attachments: Women's Suffrage in Austria and the Social Democratic Struggle for Women's Votes in Die Unzufriedene - Bargetz, Brigitte (Frontiers in Sociology, 2019)
“Human progress lies in discontent!” was the motto of the Austrian magazine "Die Unzufriedene" ("The Discontented"). It was first published in 1923 as an “independent weekly magazine” designed to reach “all women”. Yet, it was first and foremost, a Social Democratic journal, established to socialize women politically and to obtain women’s votes outside the Social Democratic purview in the 1923 National Council elections. Since women’s suffrage had been established only a few years earlier, the struggle for women’s votes was of utmost importance. This essay argues for understanding the journal as a mode and an instrument for the mobilization of affects for Social Democratic ends. Proposing the concept of affective attachments, it shows how the Austrian Social Democratic Workers’ Party (SDAP) used the journal in an ambivalent way to affectively address women and to create political moods that would attract them to the party’s political agenda.